The category of image in modern humanities: the problem and its scientific discourses - Pliasun, Olha (Current issues of Ukrainian linguistics: theory and practice, 2018)
The given article analyzes various approaches to the interpretation of the category of image in modern humanities and social sciences (e.g. politology, economics, culturology, journalism etc.). However, it is stressed that in terms of linguistics the phenomenon of image is insufficiently researched. Thus, the author notes that in linguistic discourse the category of image should be studied within the framework of a new direction of linguistic studies which is currently at the stage of forming – lingvoimageology. The primary interest of lingvoimageology is the study of linguistic mechanisms of image making. The author comes to the conclusion that in modern scientific discourse lingvoimageology is one of the most topical and promising branches of world neolinguistics.